2020
DOI: 10.1002/aic.16935
|View full text |Cite
|
Sign up to set email alerts
|

Heteroepitaxial growth of vertically orientated zeolitic imidazolate framework‐L (Co/Zn‐ZIF‐L) molecular sieve membranes

Abstract: Despite the extensive potential of zeolitic imidazolate framework (ZIF) membranes in gas separation, the development of continuous, oriented ZIF membranes onto a polymeric substrate remains a significant challenge. This is presumably due to weak adhesion, and insufficient heterogeneous nucleation sites on the polymer surface. Herein, a layer of horizontally aligned poly(sodium‐4‐styrene sulfonate)‐modified halloysite nanotubes (PSS‐HNTs) with ample nucleation sites was used for templated growth of vertically o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Please do not adjust margins Based on the above results, the CFC-assisted impregnation seeding technique allows for the formation of a more typical seeding morphology similar to those in previous studies. 40,54 In the studies of the sequence of ligand and metal solution circulation, it was found that the formation of seeds can also be controlled by rearranging the order of ligand and metal impregnation, where applying metal impregnation prior to ligand forms larger and more evident seeds on the surface (Fig. S3).…”
Section: Morphological Analysismentioning
confidence: 99%
“…Please do not adjust margins Based on the above results, the CFC-assisted impregnation seeding technique allows for the formation of a more typical seeding morphology similar to those in previous studies. 40,54 In the studies of the sequence of ligand and metal solution circulation, it was found that the formation of seeds can also be controlled by rearranging the order of ligand and metal impregnation, where applying metal impregnation prior to ligand forms larger and more evident seeds on the surface (Fig. S3).…”
Section: Morphological Analysismentioning
confidence: 99%
“…The low selectivity at high temperature indicates that the temperature should be maintained at 40°C for further membranes testing. From the previously reported works [26,39], it was concluded that the separation of the hydrocarbons through the gas separation system was affected by the high temperature, so that the low operating temperature favored the recovery of hydrocarbons from the mixed nitrogen stream. Consequently, 40°C temperature was selected for further testing of these membranes.…”
Section: Effect Of Feed Temperature and Pressurementioning
confidence: 99%
“…It is worth noticing that; besides the extensively researched linker-substituted effect, metal-substitution also influences the molecular sieving efficiency of the associated ZIF crystals. By introducing a second metal ion in the MOF cluster, the stability and affinity towards the target gases can be largely improved [39][40][41] . Many recent works have reported in which researchers have used mixed metal MOFs by adding another metal in the ZIF-8 crystal for properties enhancement 41 .…”
Section: Introductionmentioning
confidence: 99%
“…Membrane technology can efficiently separate raw reagents and products of chemical, pharmaceutical, environmental, and energy-related industries. 1,2 Benefiting from the uniform and regular nanoporous structures, polycrystalline membranes, comprising of zeolites, [3][4][5][6] metalorganic frameworks (MOFs), [7][8][9][10][11][12][13][14][15] covalent-organic frameworks, 16 and so on, show outstanding performance for precisely molecular separations.…”
Section: Introductionmentioning
confidence: 99%
“…Membrane technology can efficiently separate raw reagents and products of chemical, pharmaceutical, environmental, and energy‐related industries 1,2 . Benefiting from the uniform and regular nanoporous structures, polycrystalline membranes, comprising of zeolites, 3–6 metal–organic frameworks (MOFs), 7–15 covalent‐organic frameworks, 16 and so on, show outstanding performance for precisely molecular separations. But for the binary or multiple mixtures with small and similar molecular diameters, for example of H 2 and CO 2 with difference in kinetic diameters (KD) of only 0.4 Å, their separation through these membranes is still a tough challenge, 17 because the controlling of transport nanochannels in subatomic levels is difficult and the lattice flexibility of polycrystalline membranes causes pore variation 18,19 .…”
Section: Introductionmentioning
confidence: 99%